SOME ISSUES OF MODERNIZATION OF SOCIETY (Conference Zone, 2022)
Modernization is a process that leads to structural change, development, and improvement of social reality and it refers to all aspects of social development. The main factor of economic, social-political, spiritual and cultural modernization is initially, the emergence of scientific changes in the world